2009
DOI: 10.5194/angeo-27-669-2009
|View full text |Cite
|
Sign up to set email alerts
|

Titan's plasma environment during a magnetosheath excursion: Real-time scenarios for Cassini's T32 flyby from a hybrid simulation

Abstract: Abstract. With a Saturnian magnetopause average stand-off distance of about 21 planetary radii, Titan spends most of its time inside the rotating magnetosphere of its parent planet. However, when Saturn's magnetosphere is compressed due to high solar wind dynamic pressure, Titan can cross Saturn's magnetopause in the subsolar region of its orbit and therefore to interact with the shocked solar wind plasma in Saturn's magnetosheath. This situation has been observed during the T32 flyby of the Cassini spacecraft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…The replacement of such field lines observed at much higher altitudes probably rather involves either convection or reconnection mechanisms. We may add that Ma et al (2009) and Simon et al (2009) showed the importance of reconnection processes in the reconfiguration of the magnetotail plasma during the T32 flyby.…”
Section: Ionospheric Conductivitiesmentioning
confidence: 99%
“…The replacement of such field lines observed at much higher altitudes probably rather involves either convection or reconnection mechanisms. We may add that Ma et al (2009) and Simon et al (2009) showed the importance of reconnection processes in the reconfiguration of the magnetotail plasma during the T32 flyby.…”
Section: Ionospheric Conductivitiesmentioning
confidence: 99%
“…Any particle hitting the obstacle boundary at an altitude of 500 km above Titan's surface is removed from the simulation, whereas the implemented inner boundary conditions allow a free diffusion of the electromagnetic fields through Titan's interior. Details are discussed by Simon et al (2006b) and especially Simon et al (2009a).…”
Section: Hybrid Equations and Simulation Setupmentioning
confidence: 99%
“…In consistency with the interpretation of Cassini magnetometer data from the T32 encounter , the picture drawn by the hybrid model suggests that Titan opened Saturn's magnetopause like a comet that crosses a sector boundary in the solar wind. Moreover, Simon et al ( , 2009a show that the reconfiguration of Titan's exospheric tail during the magnetopause passage is controlled by the large gyroradii of the involved pick-up species, but the change in the upstream plasma conditions does not lead to a detachment of the tail. It should be noted that while this model considered both a change of the plasma composition (from oxygen to hydrogen) and a magnetic field reversal at the boundary layer between both plasma regimes, the magnetospheric as well as the magnetosheath flow possessed a magnetosonic Mach number that is smaller than M S =1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations